2014
DOI: 10.4049/jimmunol.1300755
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inhibition of Complement and CD14 Efficiently Attenuated the Inflammatory Response Induced byStaphylococcus aureusin a Human Whole Blood Model

Abstract: The complement and TLR systems are activated in sepsis, contributing to an unfavorable inflammatory “storm.” Combined inhibition of these systems has been documented to efficiently attenuate the inflammatory responses induced by Gram-negative bacteria. In this study, we hypothesized that the combined inhibition would attenuate the inflammatory responses induced by Gram-positive bacteria. Staphylococcus aureus bacteria (strains Cowan and Wood), as well as S. aureus cell wall lipoteichoic acid (LTA), were incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 54 publications
6
33
0
Order By: Relevance
“…Taken together, these data indicate that initial phagocytosis of C. albicans strongly depends on C5a-induced upregulation of CR3. This finding, together with available data for Escherichia coli and Staphylococcus aureus, supports a predominant function of C5a in the innate immune responses toward systemic infection in general (23,30). Following a longer coincubation, PMN effector mechanisms (e.g., phagocytosis of C. albicans and oxidative burst) appeared to be C5a-independent and mainly influenced by other stimuli, whereas the secretion of secondary granule contents (lactoferrin, NGAL) from PMN with no fungal contact could be blocked by anti-C5a Ab treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Taken together, these data indicate that initial phagocytosis of C. albicans strongly depends on C5a-induced upregulation of CR3. This finding, together with available data for Escherichia coli and Staphylococcus aureus, supports a predominant function of C5a in the innate immune responses toward systemic infection in general (23,30). Following a longer coincubation, PMN effector mechanisms (e.g., phagocytosis of C. albicans and oxidative burst) appeared to be C5a-independent and mainly influenced by other stimuli, whereas the secretion of secondary granule contents (lactoferrin, NGAL) from PMN with no fungal contact could be blocked by anti-C5a Ab treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Similar models have been successfully applied to study complement function in the early immune response against bacterial pathogens and used whole blood anticoagulated with the highly specific thrombin inhibitor lepirudin (28)(29)(30). In contrast to other anticoagulants, lepirudin has been shown to preserve complement activity and thus allows physiological immune activation (23).…”
Section: Discussionmentioning
confidence: 99%
“…2E). The mechanism for the enhanced phagocytosis is likely TLR2-mediated activation of the CR3 (CD11b/CD18), as S. aureus phagocytosis in the whole blood model is strongly Cdependent (27) and the CD11b level on both monocytes and granulocytes increased strongly upon TLR2 stimulation (Fig. 2F).…”
Section: Tlr2 Ligands Antagonize the Induction Of Ifn-b By S Aureus mentioning
confidence: 99%
“…We have earlier shown that the inflammatory reaction induced by both E. coli and S. aureus in human whole blood can be attenuated by combined inhibition of CD14 and one of the key complement components (14,16). To evaluate whether bacteria-induced EC activation also would be reduced by this regimen, we incubated whole blood on EC monolayers with either E. coli (10 5 bacteria/ml) or S. aureus (10 7 bacteria/ml) in addition to blocking mAbs to CD14 and C5, alone or in combination (Fig.…”
Section: Inhibition Of Bacteria-induced Ec Activation In Whole Bloodmentioning
confidence: 99%
“…We have earlier shown that combined inhibition of CD14 and one of the key complement components, at the level of either C3 or C5, can more or less completely attenuate cytokine release and leukocyte activation in whole blood after bacteria-induced activation both with Gram-negative and Gram-positive bacteria (14)(15)(16). Furthermore, in a murine sepsis model, we have recently shown that combined inhibition reduces both inflammation and mortality (17).…”
mentioning
confidence: 99%